Electron spectrum of gapless semiconductors - Tsidilkovski, Isaak M. (Springer series in solid-state sciences, 1997)
Electron Spectrum of Gapless Semiconductors presents the peculiarities of physical properties of a comparatively new class of solids - gapless semiconductors (GS). These peculiarities are determined by the main feature of the elctron spectrum, namely the absence of a gap between the conduction and valence bands. GSs form a boundary between metals and semiconductors. On the other hand GSs are of practical interest since they are very sensitive to impurities, and to the influence of light, magnetic and electric fields, and pressure.